1D MOF‐Derived N‐Doped Porous Carbon Nanofibers Encapsulated with Fe3C Nanoparticles for Efficient Bifunctional Electrocatalysis. Issue 6 (3rd February 2020) - Liu, Jiang‐Tao; Xie, Yan; Gao, Qiang; Cao, Fu‐Hu; Qin, Ling; Wu, Zhen‐Yu; Zhang, Wang; Li, Hao; Zhang, Chuan‐Ling
Abstract : A facile yet efficient approach is introduced to rationally integrate Fe3 C nanoparticles with Fe‐N‐doped mesoporous carbon nanofibers (denoted as Fe3 C@FeN@CNF) by the direct‐electrospinning technique and a subsequent calcination process. Benefiting from the unique one‐dimensional structure with high porosity and the synergies among the active sites of Fe‐Nx, N‐C and graphitic carbon encapsulated Fe3 C/Fe nanoparticles, the hierarchically structured Fe3 C@FeN@CNF show enhanced electrocatalytic activity and durability for oxygen reduction and evolutionreactions, comparable to that of commercialized Pt/C and RuO2 electrocatalysts. Significantly, the as‐fabricated Fe3 C@FeN@CNF composite shows higher electrochemical performance than Pt/C in the Zn‐air battery. Abstract : Hierarchically structured porous carbon nanofibers with high graphitization degree and evenly distributed active sites (Fe‐Nx, N‐C, and graphitic carbon encapsulated Fe3 C/Fe nanoparticles) have been easily prepared by direct electrospinning of metal‐organic framework nanoparticles and an iron precursor. They show high electrocatalytic performance for oxygen reduction and evolution reactions.